2010
DOI: 10.4332/kjhpa.2010.20.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Fundus Examination in Diabetes Mellitus Patients

Abstract: The purpose of this study is to analyze the proportion of fundus examination of DM patients for preventing microvascular complication and to examine the factors related to fundus examination in DM patients. This study used 2005 Korean national health and nutrition survey data. We selected all 1,129 diabetes mellitus patients from the data. And we choose 8 factors related to diabetes mellitus patients. These are sex, age group, type of residential area(rural or urban), education level, income level, comorbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This may explain differences in the use of healthcare services and glycaemic control capacity, which may be influenced by the characteristics of the individual (eg, education and income level). Several studies have found low SEPs to be associated with a greater likelihood of having higher HbA1c levels62 and a smaller likelihood of receiving eye examinations for diabetes than high SEPs 6 63 64. Also, there was an inverse association between diabetes knowledge and glycaemic control among low-income patients with diabetes 65…”
Section: Discussionmentioning
confidence: 99%
“…This may explain differences in the use of healthcare services and glycaemic control capacity, which may be influenced by the characteristics of the individual (eg, education and income level). Several studies have found low SEPs to be associated with a greater likelihood of having higher HbA1c levels62 and a smaller likelihood of receiving eye examinations for diabetes than high SEPs 6 63 64. Also, there was an inverse association between diabetes knowledge and glycaemic control among low-income patients with diabetes 65…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies (10)(11)(12)(13) indicated the disease duration of diabetes, age, education level, residential area, income level, diabetes education, and subjective health status were factors associated with the fundus examination of diabetic patients. Moreover, other studies reported that sex, age, hospitalization experience, and comorbidities were related to receiving using the glycated hemoglobin test (14,15).…”
Section: Introductionmentioning
confidence: 98%